(x+5)-(2x+3)=0

Simple and best practice solution for (x+5)-(2x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+5)-(2x+3)=0 equation:


Simplifying
(x + 5) + -1(2x + 3) = 0

Reorder the terms:
(5 + x) + -1(2x + 3) = 0

Remove parenthesis around (5 + x)
5 + x + -1(2x + 3) = 0

Reorder the terms:
5 + x + -1(3 + 2x) = 0
5 + x + (3 * -1 + 2x * -1) = 0
5 + x + (-3 + -2x) = 0

Reorder the terms:
5 + -3 + x + -2x = 0

Combine like terms: 5 + -3 = 2
2 + x + -2x = 0

Combine like terms: x + -2x = -1x
2 + -1x = 0

Solving
2 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -1x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -1x = 0 + -2
-1x = 0 + -2

Combine like terms: 0 + -2 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| -5x-7=3+5x | | -3(1+8x)=23+2n | | -2x-15-2x= | | 5-n=-3n+5 | | 8x+5=2x+7 | | R=26x | | X*1+X= | | 26=15+v | | c/5=-11/6 | | -15x+11x-3=1-5(x+1) | | 3(y+6)=2y-2 | | 6=0x | | x+(x+1)=(x+2)-(x-1) | | 3-t/6=7 | | C=81000+18x | | 11a+9a=4a+30 | | 5w^2-2w+3=0 | | x^2+18x+90x=0 | | (7t-3)-(3t+1)=-3(1-3t) | | -2-42=x | | 5.60+.25x=19.85 | | 45x-11=250 | | 2x^2+16x+5= | | x*x+12x+32=0 | | 5(3p-5)+4p=5p-6(p+4) | | 14*30b=-196 | | 176-0.8a=122+a | | 5x+2(3x-4)=80 | | 8x+4y=22 | | -17=v | | 3x+50i=18-5yi | | 45-11x=250 |

Equations solver categories